Perceived parental care during childhood, ACTH, cortisol and nicotine dependence in the adult. (30th November 2016) - Gerra, Gilberto; Manfredini, Matteo; Somaini, Lorenzo; Milano, Giulia; Ciccocioppo, Roberto; Donnini, Claudia
Abstract: Studies evidenced the relationship between adverse childhood experiences (ACEs) and tobacco smoking in adulthood. An appropriate parenting style has been found to be associated with children's less frequent tobacco consumption. Hypothalamus-pituitary-adrenal (HPA) axis hyperactivity could represent the potential link between ACEs, mood disorders and smoking susceptibility. We studied a sample of 50 male smokers, affected by nicotine dependence and 50 controls who never smoked. Self-reported retrospective perception of neglect (Child Experience of Care and Abuse: CECA-Q questionnaire), age of smoking onset, number of cigarette/day, psychiatric symptoms (Symptoms Check List 90 scale: SCL 90) and basal level of ACTH and cortisol have been evaluated. Total SCL-90 scores, CECA-Q values and cortisol plasma level were significantly higher among smokers. Cortisol and ACTH values showed a significant direct correlation with CECA-Q and SCL90 total score and an inverse significant correlation with the age of smoking. Cortisol and ACTH did not correlate with the number of cigarette smoked. Once controlled for SCL90 and CECA-Q with multiple regression measures, the association between smoking and hormone levels reversed, suggesting that increased cortisol and ACTH basal levels were attributable to preexisting conditions such as early-life exposure to emotional neglect, psychological problems and a predisposition to addictive behavior. Highlights: Association between tobacco smoke and poor parenting in childhood history. Increased HPA axis function among smokers in comparison to abstinent subjects. Direct correlation with ACEs and psychiatric symptoms, stress hormones. Inverse correlation between ACEs, cortisol, tobacco dependence age of onset. Enhanced HPA axis tone was attributable preexisting condition linked to ACEs.